An Analytical Approach to User Based Studies of Five JNV’s Libraries of West Bengal:Stark Realities - Chakrabarti, Abhijit; Sardar, Sudin Kumar (Journal of Information and Knowledge, 2016)
User study needs a significant amount of time and effort. The understanding of user’s behavior may be achieved through a particular user study. The paper discusses the prerequisite of user study in the recent information technology enabled environment where libraries have to face a great challenge. The present study covers five selected Jawahar Navodaya Vidyalayas of West Bengal situated in Howrah, Mursidabad, Durgapur, Nadia and Bankura. The main objective of JNV’s Library is to computerize library operations and services and to develop library infrastructure for providing equitable services to all of its students and staff of JNVs. Libraries serve as a center for providing the right information to the right people at all times. Evaluation of the library and information services is one of the major concerns and an integral part of library and information science practitioners. User studies are to be recognized as an important part of the information packages. Information providers like the library and information centers need to be aware of their users’ information requirements as well as their information seeking and information retrieving methods in order that they might be able to provide better services. This paper presents the library services and its users in JNVs Libraries. This study examines several aspects of library use, including frequency of visiting the library, user satisfaction from library services and library collection. The study also covers the use of computer base services in the library. Some suggestions are also provided on the basis of study for enhancing the user satisfaction level. The understanding of user behavior that can be gained through a particular user study must be valuable enough, in terms of improving the practice of library professionals. A rationale for evidence based librarianship, based on studies of user behaviors and the information needs that motivate those behaviors will be presented. This paper undertakes to study the library services and its user’s behavior in JNV libraries.